The Development of Adolescent Empowerment for Health Promotion: A Scoping Review - Iacobini, Virginia; Mazza, Eduardo; Rinaldi, Marilena; Galletti, Caterina (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Empowering adolescents has emerged as a critical strategy in health promotion, with significant implications for their well-being and development. Aim. This study aims to map the existing literature related to adolescent empowerment and identify the fundamental elements that need to be considered in the process of health promotion to improve the lifestyle and well-being of adolescents.Methods. A scoping review was conducted following the methodology outlined by Arksey and O’Malley. The reporting process was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews checklist. The literature research was performed in the PubMed, CINAHL, and Scopus databases. Additionally, grey literature sources were manually searched. The keywords “adolescent,” “empowerment,” “development model”, and “health promotion” were used, combined with the Boolean operators “AND” and “OR” to refine the search strategy.Results. The present study reviewed nine studies that highlight the multifaceted nature of empowerment in health promotion, with cultural, contextual and systemic factors influencing its effectiveness. Programs integrating participatory methodologies and aligning with adolescents’ lived experiences show the greatest promise.Conclusion. Adolescent empowerment is a powerful mechanism for advancing health promotion goals. By equipping young individuals with the tools and autonomy to make informed decisions, health interventions can achieve lasting impact. Future research should prioritize culturally adaptable frameworks and metrics to assess the sustainability of empowerment outcomes in diverse settings.